Parametric analysis of the drag produced by a VHBR engine using CFD - Gomez-Parada, Josue (Cranfield University, 2009)
The future of the civil aeronautics industry will be determined by the decreasing oil supplies around the world and by more environmentally friendly aircraft designs. Future Gas Turbine engines are being designed focusing on the fuel economy reducing emissions and noise. This project is on the application of Computational Fluid Dynamics (CFD) techniques to the computation and parametric analysis of drag produced by the nacelle of Very High By-pass Ratio (VHBR) engines as integrated into the airframe. Engines based on VHBR concept are consistent with the objectives of VITAL which is an EU project for creating environmentally friendly engine without SFC penalties or impairing other benefits. Three main architectures for the fan were considered for the task, a geared turbofan, contra rotating turbofan and direct drive turbofan. The long range geared turbofan is the one considered in this project. Increasing the BPR for turbofan engines is one of the best options for decreasing the SFC and noise produced by the power plant, unfortunately there are some issues to be considered. One of the major drawbacks when the BPR reaches very high values (VHBR) is the integration to the airframe because of the very large size of the fan. The drag produced by the nacelle has to be countered with propulsive force and therefore decreasing the propulsive efficiency and increasing the SFC. CFD can be used for parametric analysis of drag produced by turbofan nacelles. The analysis was carried out in 3 basic stages. 2D geometry analyses of the afterbody and forebody are the first stage. Small changes to the basic geometry parameters were made in order to form conclusions about which parameters are more significant for drag generation in each section of the nacelle. In the second stage of the project a 3D geometric analysis was carried out with the whole nacelle. The important parameters from the 2D simulations and some of the parameters required for 3D geometry were varied in the analysis. Conclusions were made about the influence of each of the parameters in drag generation and their influence on the interaction between forebody and afterbody. In the third stage of the project, the influence on drag of the positioning of the engine relative to the wing is analyzed. No geometry changes were made and no pylon was used. Conclusions were made from the changes of pressure distribution and supersonic zones and their impact on the drag.